Nilai-Nilai Toleransi dalam Al-Qur'an (Analisis Semiotik Roland Barthes Terhadap QS. Al-Kafirun [109]: 1-6 dan QS. Al-Hujurat [49]: 103) - Julianti, Nesha; Firdaus, Hasan (LPPM IAI PERSIS GARUT, 2024)
This study aims to uncover the meaning of denotation and connotation in QS. Al-Kafirun [109]: 1-6 and QS. Al-Hujurat [49]: 13, as well as the relevance of the social, cultural, or religious context of Indonesian society to the two suras/verses above. This research is qualitative research, with the type of literature study research (Library research), which is reviewing books, literature, notes, closely related to the problem to be solved. In analyzing the data of this study, using Roland Barthes' semiotics, namely two levels of significance. First, denotation that examines the scope of language. Second, connotation or analysis of myth, the study of which relates to the internal text of the Qur'anic verse, so that the ideology that surrounds it can be found. The results of this study, in QS. Al-Kafirun [109]: 1-6 contains inclusivism, stating and believing that truth is found only in one's own religion, but at the same time having a tolerant attitude towards religion, or thinking that is different from what we believe. While in Q.S Al-Hujurat [49]: 13 contains the notion of egalitarianism, namely the belief in the principle of equality or equal rights to be able to achieve welfare and equal opportunities in the social, economic, legal, political domains. In addition, there is relevance of Indonesian society to the two ideologies contained in the surah / verse above, namely believing in inclusive religious beliefs, accepting plurality, and applying egalitarian principles. Thus, the ideology of inclusivism and egalitarianism is relevant to Indonesian society which tends to be pluralist.